Edukasi Dampak Demam Berdarah Dengue (DBD) Dalam Meningkatkan Pengetahuan dan Sikap Masyarakat di Kelurahan Tanjung Karang - Halid, Musparlin (Jurnal Pengabdian kepada Masyarakat UBJ, 2022)
Dengue Hemorrhagic Fever (DHF) is a disease caused by the dengue virus which is transmitted through the bite of the Aedes aegypti mosquito and the incidence depends on the geographical location and local climate. With the development of cases of DHF, it is necessary to have a special breakthrough to improve the quality of life of the community because it has a very significant impact on life safety and its impact on the socio-economic family. Educational activities are carried out using lecture, discussion and question and answer methods. Most of the people in the Tanjung Karang environment are still lacking in knowledge regarding the prevention of dengue fever, so many people have never handled mosquito larvae at home, even though this method is very effective in preventing the occurrence of dengue fever.